ANALISIS PEMANFAATAN SOCIAL MEDIA MARKETING TERHADAP CUSTOMER LOYALTY YANG MENGGUNAKAN BRAND TRUST SEBAGAI VARIABEL MEDIASI - Anggraeni, Ruri; Layaman, Layaman; Djuwita, Diana (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This research is motivated by the results of the Hootsuite (We are Social) Survey which revealed that there are 56% of Bank customers who use social media. This study aims to determine the use of social media marketing to brand trust and its impact on brand trust and customer loyalty. Data collection through the distribution of questionnaires to Islamic Bank customers. The analysis technique used is path analysis. The results showed that Social Media Marketing a positive and significant effect on brand trust. In addition, Brand Trust and Social Media Marketing partially have a positive and significant effect on Customer Loyalty. And, indirectly that Social Media Marketing towards Customer Loyalty is mediated by Brand Trust. Managerial implications were found in this study.